The Wished-For Children: Do Mothers Carry the Burden While Fathers Reap the Joy? - Mathias Huebener; Reto Odermatt (Institute of Labor Economics (IZA), 2025)
We assess the gendered effects of having children on well-being, careers, and the division of domestic work. As exogenous variation in parenthood, we exploit the quasi-random success of in-vitro fertilisation (IVF) treatments. Children increase mothers' well-being only in the short term, while fathers experience longer-lasting gains. However, only mothers show a persistent decline in labor supply and a rise in domestic work. Their satisfaction with the division of work declines, and they are more likely to perceive it as unfair, implying that the new equilibrium in the division of work deviates from mothers' preferences.
Keywords: I31; J13; J16; J22; 330; IVF treatment; gender inequality; well-being; parenthood; child penalty